2014
DOI: 10.1002/2013jd020453
|View full text |Cite
|
Sign up to set email alerts
|

Active fires from the Suomi NPP Visible Infrared Imaging Radiometer Suite: Product status and first evaluation results

Abstract: The Visible Infrared Imaging Radiometer Suite (VIIRS) sensor on the Suomi National Polar-orbiting Partnership (S-NPP) satellite incorporates fire-sensitive channels, including a dual-gain high-saturation temperature 4 μm channel, enabling active fire detection and characterization. The active fire product, based on the 750 m moderate resolution "M" bands of VIIRS, is one of the standard operational products generated by the Interface Data Processing Segment of the S-NPP ground system. The product builds on an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
89
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(90 citation statements)
references
References 51 publications
0
89
0
1
Order By: Relevance
“…VIIRS nocturnal fire detection is primarily based on MWIR bands (Giglio et al, 2003), following the suit from MODIS fire products (Csiszar et al, 2014). The choice of primary spectral band by these products is one of the most important factors responsible for the remarkable difference in detections between VNF and other fire products eventually.…”
Section: Reconciliation With Replication and Sensitivity Analysis Of mentioning
confidence: 99%
See 1 more Smart Citation
“…VIIRS nocturnal fire detection is primarily based on MWIR bands (Giglio et al, 2003), following the suit from MODIS fire products (Csiszar et al, 2014). The choice of primary spectral band by these products is one of the most important factors responsible for the remarkable difference in detections between VNF and other fire products eventually.…”
Section: Reconciliation With Replication and Sensitivity Analysis Of mentioning
confidence: 99%
“…The capability of these bands highlighted by them for fire monitoring formed the basis of many fire detection algorithms (MODIS, VIIRS, AVHRR etc.) developed afterwards (Weaver et al, 2004;Giglio et al, 2003;Csiszar et al, 2014). A limitation of the fire algorithms based on MWIR and LWIR bands is that the measured brightness temperature is dependent on the background temperature which means the total radiance observed by the satellite instrument is the result of both burning (subpixel fire) and non-burning fractions (background) of the ground pixel.…”
Section: Introductionmentioning
confidence: 99%
“…Spaceborne remote sensing offers spatially continuous fire detection and observation at sub-daily temporal resolution without jurisdictional barriers. The moderate resolution imaging spectroradiometer (MODIS) [37], visible infrared imaging radiometer suite (VIIRS) [38,39], and Landsat operational land imager (OLI) [40] are examples of such sensor platforms. Each sensor platform produces a slightly different fire occurrence and extent database dependent upon its frequency of acquisition for a given location, the spectral wavelengths it collects data over, the spatial resolution of data collection, and historical availability of the sensor.…”
Section: Retrospective Vulnerability Assessment Measuring Exposure Thmentioning
confidence: 99%
“…Dozier [5] demonstrated the detection of a sub-pixel hot source and its characterization in terms of temperature and area from nighttime remote sensing data at two infrared wavelengths, between which there exists a significant contrast in the thermal radiation by the hot target. The technique has been applied to detect fires and to determine the subpixel size of the active fire(s) and average fire temperature using the Visible Atmospheric Sounder (VAS) sensor on the Geostationary Orbiting Environmental Satellite (GOES) [6,7], the NOAA Advanced Very High Resolution radiometer (AVHRR) sensors [8,9], the Visible and Infrared Spectrometer (VIRS) on the Topical Rainfall Measuring Mission (TRMM) [10], the Moderate-Resolution Imaging Spectroradiometer (MODIS) sensors [11,12] and the Visible Infrared Imaging Radiometer Suite (VIIRS) on the Suomi National Polar-orbiting Partnership satellite [13]. Through a sensitivity analysis, Giglio and Kendall [14] found that systematic retrieval errors can become enormous when the size fraction of the active fire is <0.005.…”
Section: Introductionmentioning
confidence: 99%